Prevalence and associated factors of psychiatric problems in children aged 6–18 years with type-1 diabetes mellitus in Gondar, Ethiopia: a cross-sectional study - Birhanu AlehegnAwoke; Geta Bayu Genet; Addisu Ginbu Dubie; Biruk Fanta Alemayehu; Mehretie Kokeb Alemu (BMC Endocrine Disorders)
Abstract Background Diabetes mellitus is one of the most common chronic illnesses in children with multiple psychosocial, economic and developmental effects. Psychiatric disorders such as depression, anxiety, psychological distress, and eating disorders are more common in diabetic patients than the non-diabetic once. The main objective of our study was to assess Prevalence and associated factors of psychiatric problems in children aged 6–18 years with type 1 diabetes mellitus in Gondar, Ethiopia. Methods An institution-based cross-sectional study was conducted among 206 children aged 6–18 years with type-1 diabetes mellitus having regular follow-ups at the University of Gondar comprehensive and Specialized Hospital (UoGCSH) over three three-month period. Data was collected by trained physicians using interviewer-administered structured questionnaires. Convenient sampling technique was applied and Participants were selected sequentially until the sample size was achieved. Both bivariate and multivariate logistic regression analyses were used for Model fitness and the strength of association was determined using an OR, p-value of < 0.05 and 95% CI. Results The prevalence of psychiatric problems was 11.7% and those children living with only either of the parent (AOR = 8.39, 95%: 1.5–46), living with other relatives (AOR = 11.3, 95% CI: 1.97–64.7), more than 5 family size (AOR = 0.3, 95%CI: 0.1–1.2), fathers attended formal education (AOR = 0.3, 95%: 0.04–1.73), a patient having good glycemic control (AOR = 0.2, 95%: 0.04–0.67) and those with a family history of diabetes mellitus(AOR = 5.2, 95% CI: 1.2–22.1) were significantly associated with a psychiatric problem in diabetic aged 6–18 years with p-value < 0.05. Conclusion The prevalence of psychiatric problems in diabetic children was significantly high and children living with single parent, paternal educational status, glycemic control, family history of diabetes, and family size were found to have significant association with the occurrence of psychiatric problems in diabetic children.